Performance information - the critical issue of public finance legal regulation - S. O. Shokhin; E. V. Kudryashova (Правоприменение)
The subject. The paper is focused on the study of the role of performance information in the decision-making process on public finance with particular accent on the legal aspects of the issue.The purpose. We aim to show that the performance results have a little impact on the public finance allocation in the next management cycle. Nowadays the financial resolutions are taken not on the basis of the results, but apart from them. The problem can be identified in many countries and currently discussed on the international level. We make an attempt to identify the main reasons for this. The research is elaborating the possible solutions for the problem and presenting possible amendments to the legislation.The methodology. The multidisciplinary approach is employed in this research as the problem is covered by different social sciences like law, economics and politics. The methods of analysis and synthesis are relevant for this paper. The examples and illustrations from different countries all over the world constitute the empirical part of the article.The main results and conclusions. The key reason for the omission or misuse of performance results in public finance is the passive role of the user of the performance information. There is a lack of legal incentives for using the performance results for those who take the financial decisions. Those who take the decisions in public finance governance should have an obligation to assess the performance information and use it for the further resolutions.Scope of the research outcome application. This research shall have substantial impact on the development of adequate legal model for the performance information use in public finance allocation. If the legal obligation to use the performance information is introduced it will have positive impact on the legal regulation of public finance in Russia. This can be relevant for the international studies of the issue and for the legal regulation of financial governance in other countries as well.